Conjoint Measurement Methods and Applications - Gustafsson, Anders; Herrmann, Andreas; Huber, Frank (Springer Berlin Heidelberg : Imprint: Springer, 2007)
The book covers all recent developments in Conjoint Analysis. Leading scientists present theory and applications of this technique. In short, the following models, techniques, and applications are discussed: normative models that maximize return, extension of choice-based conjoint simulations, latent class, hierarchical Bayes modelling, new choice simulators, normative models for representing competitive actions and reactions (based on game theory), applications in diverse areas, computation of monetary equivalents of part worth, share/return optimisation (including Pareto frontier analysis), coupling of conjoint analysis with the perceptual and preference mapping of choice simulator results.